Aesthetic dilemmas encounters with art in Hugo von Hofmannsthal’s literary modernism - Burks, Marlo A. 1986- (McGill-Queen’s University Press, 2023)
"Hugo von Hofmannsthal (1874-1929) is frequently portrayed in cultural histories as an aloof writer with a precious style, out of step with modern sensibilities. In Aesthetic Dilemmas Marlo Burks reassesses Hofmannsthal’s oeuvre and its place in twentieth-century European modernist aesthetics. Through an examination of a diverse range of Hofmannsthal’s ekphrastic writings – including poetry, essays, opera libretti, fiction, and letters – Burks argues that Hofmannsthal’s work aims to engage the consciousness and sensibility of readers, listeners, and viewers by way of dynamic encounters with works of art. Aesthetic Dilemmas thereby corrects a long-standing, flawed characterization of Hofmannsthal’s work as escapist and demonstrates how his place in the Modernist movement has been misunderstood in most scholarship. The book is in dialogue with a broad range of critical voices and treats a variety of themes, from aestheticism to money, interpersonal relationships, suffering, poverty, labour, futurity, legacy, and hope. Translating numerous passages into English for the first time, Aesthetic Dilemmas gives English-speaking readers the chance to evaluate Hofmannsthal’s literary merit and his contributions to the enduring conversation about art’s relation to ethics."